Axonal mRNA localization and local translation in neurodegenerative disease - Jin-Xin Lu; Yang Wang; Yi-Jie Zhang; Mei-Fen Shen; Hai-Ying Li; Zheng-Quan Yu; Gang Chen (Neural Regeneration Research, 2021)
The regulation of mRNA localization and local translation play vital roles in the maintenance of cellular structure and function. Many human neurodegenerative diseases, such as fragile X syndrome, amyotrophic lateral sclerosis, Alzheimer’s disease, and spinal muscular atrophy, have been characterized by pathological changes in neuronal axons, including abnormal mRNA translation, the loss of protein expression, or abnormal axon transport. Moreover, the same protein and mRNA molecules have been associated with variable functions in different diseases due to differences in their interaction networks. In this review, we briefly examine fragile X syndrome, amyotrophic lateral sclerosis, Alzheimer’s disease, and spinal muscular atrophy, with a focus on disease pathogenesis with regard to local mRNA translation and axon transport, suggesting possible treatment directions.